2022
DOI: 10.1136/heartjnl-2021-319603
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and thrombotic valvulopathies in autoimmune disease

Abstract: Rheumatologic diseases are characterised by loss of immune tolerance, resulting in systemic inflammation. Inflammation and scarring of the endocardium, which lines the inner surface of the heart chambers and valves, can result in valvular thickening and dysfunction. Estimates of prevalence vary depending on the sensitivity of the screening methodology used and range from 30%–50% in systemic lupus and rheumatoid arthritis to 10%–30% in ankylosing spondylitis. Progression of valve disease is a slow process but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Aortic valve insufficiency is one of the most important cardiovascular involvements occurring in 18% of patients [ 50 ]. It has been proposed to be a result of chronic aortitis which involves the aortic root and leads to a dilatation and insufficiency [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aortic valve insufficiency is one of the most important cardiovascular involvements occurring in 18% of patients [ 50 ]. It has been proposed to be a result of chronic aortitis which involves the aortic root and leads to a dilatation and insufficiency [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pathomechanism of valvulopathies is not yet fully understood. Based on the histological examination of the autopsy samples, mononuclear cell infiltration, endothelial cell proliferation, platelet activation and mycrothrombus formation can be observed [ 10 ]. It has been suggested that APA positivity increases the risk of valve thrombi formation, which may explain the association of APAs with valvular lesions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our data, we found the strongest association between the presence of anticardiolipin IgG antibodies and non-thrombotic cardiac manifestations. Based on the results of a recently published meta-analysis, patients with anticardiolipin IgG antibodies can benefit the most from echocardiography screening tests [ 10 ]. At the same time, the incidence of ischemic heart disease and cardiomyopathy was significantly higher in patients with valvulopathy, which draws attention to the fact that non-thrombotic cardiac manifestations can occur not only independently but also in combination with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with axSpA have a 4.5-fold higher frequency of aortic valve insufficiency than controls (aHR = 4.5, 95% CI 1.1–13.6) [38]. This may be the result of chronic aortitis leading to aortic root dilatation and valve insufficiency [24,39] and can occur in up to 18% of patients with axSpA [40].…”
Section: Axial Spondyloarthritismentioning
confidence: 99%